Magnesium-potassium composite agricultural water-absorbing resin and preparation method thereof
Patent Information
- Application Number
- CN202610926372.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-09-25
AI Technical Summary
[0009]为解决现有技术中吸水树脂在复杂土壤环境中稳定性差、离心保留能力不足及吸水性能与结构强度难以协同提升的问题,本发明提出了一种基于镁离子与有机-无机复合结构的镁钾复合型农业吸水树脂及其制备方法
[0019]相比于现有技术,本发明至少具有以下有益效果:本发明通过镁-聚丙烯酸钾络合相、聚乙烯醇/氢氧化镁有机-无机复合相以及偏高岭土基有机-无机吸水组分的复配,构建了多组分协同的复合吸水体系,使材料兼具较高吸水倍率和较好的结构稳定性。本发明中,Mg2+在非强碱条件下可与聚丙烯酸钾分子链上的羧酸盐基团形成离子配位作用,有助于提高树脂颗粒的结合强度、离心保留量和抗溶解流失能力。与未引入镁盐的对比例相比,本发明样品的溶解损失率更低、离心保留性能更好。本发明将镁盐在碱性聚乙烯醇体系中转化为氢氧化镁无机相,使其作为无机增强组分分散于聚乙烯醇相中,通过表面羟基作用或界面氢键作用提高复合体系的结构完整性,从而改善吸水后材料的抗塌陷能力和颗粒稳定性。本发明引入经硅烷偶联剂处理的偏高岭土基有机-无机吸水组分,硅烷偶联剂有助于增强偏高岭土无机相与丙烯酸盐/丙烯酰胺共聚网络之间的界面结合,降低复合材料在吸水和释水过程中的界面剥离风险,使材料在碱性介质中仍能保持相对较好的吸水能力。本发明所得树脂在去离子水和碱性溶液中均具有一定吸液能力。虽然碱性环境下因电解质效应和高pH作用使吸水倍率低于去离子水体系,但实施例样品仍表现出较高的碱性吸水倍率,说明其复合网络结构具有较好的环境适应性。本发明所得树脂具有较好的土壤保水效果。将其加入沙壤土后,可提高7d残余水量,延缓水分蒸发和迁移,适用于农业保水、抗旱节水及肥水保持等应用场景。本发明制备方法以水相复合、常规加热搅拌、脱水、干燥、粉碎和造粒为主要工艺,步骤清晰,原料易得,适合进一步放大制备和农业保水材料推广应用。
Smart Images

Figure CN122810307A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of polymer water-absorbing materials and agricultural water-retaining agents. Specifically, it relates to a magnesium-potassium composite agricultural water-absorbing resin and its preparation method. Background Technology
[0002] With the increasing severity of global climate change and water scarcity, agricultural production faces multiple challenges, including frequent droughts, uneven spatial and temporal distribution of precipitation, and low water use efficiency. Particularly in arid, semi-arid, and desertified regions, poor soil water retention capacity and significant evaporation losses severely restrict crop growth and yield. Therefore, developing efficient, stable, and environmentally friendly soil water-retaining materials has become an important research direction in modern agriculture.
[0003] Superabsorbent polymers (SAPs) are functional materials capable of absorbing and retaining hundreds of times their own weight in water, and have been widely used in agricultural water retention, horticultural substrate improvement, and ecological restoration. Traditional agricultural SAPs are mostly based on polyacrylates, which form a three-dimensional network structure through covalent cross-linking, resulting in a high water absorption rate. However, these materials still have some shortcomings in practical applications: firstly, their water absorption capacity decreases significantly in saline or alkaline environments; secondly, some resins lack structural stability after water absorption, easily dissolving or losing their structure, or experiencing a decrease in mechanical strength, affecting long-term performance. Furthermore, single organic polymer networks are prone to degradation or migration in soil, making it difficult to balance water absorption capacity and structural stability.
[0004] To address these issues, researchers have attempted to enhance the stability of the network structure by introducing multivalent metal ions to achieve ionic cross-linking. For example, magnesium ions (Mg...) 2+ Ionic crosslinking can form coordinate bonds with carboxyl groups, thereby constructing reversible or semi-reversible crosslinking points, improving the material's resistance to swelling and centrifugal retention. However, systems relying solely on ionic crosslinking often suffer from insufficient water absorption capacity, making it difficult to meet the high water absorption requirements of agriculture. Furthermore, single polyacrylate systems are prone to performance degradation in alkaline soils or high-electrolyte environments.
[0005] On the other hand, combining organic polymers with inorganic materials has proven to be an effective way to improve the overall performance of absorbent materials. Natural clay minerals (such as metakaolin) have good specific surface area and structural stability, and can serve as an inorganic framework to improve the mechanical properties and resistance to water loss of materials. Simultaneously, modifying inorganic surfaces with silane coupling agents can enhance the interfacial bonding between them and the organic polymer network, constructing a stable organic-inorganic composite structure. Furthermore, introducing monomers such as acrylic acid and acrylamide for free radical copolymerization can form a dense and stable covalent cross-linked network, thereby significantly improving the water absorption capacity and salt and alkali resistance of the material.
[0006] Although the above modification strategies have improved the performance of water-absorbing resins to some extent, the existing technologies still have the following problems: First, multiple modification methods are often used alone, making it difficult to achieve synergistic optimization of water absorption performance, structural stability and environmental adaptability; Second, the interfacial bonding between different components in the composite system is insufficient, which can easily lead to delamination or structural instability of the material in practical applications; Third, some preparation processes are complex and costly, which is not conducive to large-scale agricultural promotion and application.
[0007] Furthermore, in practical agricultural applications, water-absorbing resins not only need to possess high water absorption rates, but also good moisture retention capabilities, compressive and shear strength, and low dissolution loss rates to prevent runoff during irrigation or rainfall. Simultaneously, in alkaline or saline soils, the material must maintain high water absorption and release properties to adapt to the varying soil environments of different regions. Therefore, developing a structurally stable, high-quality water-absorbing composite agricultural water-absorbing resin suitable for complex soil environments is of great significance.
[0008] In summary, there is an urgent need to provide a new agricultural water-absorbing resin and its preparation method. By rationally constructing an organic-inorganic composite network and introducing a multivalent metal ion structure, the water absorption rate can be increased while enhancing the structural stability and environmental adaptability of the material. This overcomes the problem of difficulty in balancing water absorption capacity and stability in existing technologies and meets the application needs of modern agriculture for high-efficiency water-retaining materials. Summary of the Invention
[0009] To address the problems of poor stability, insufficient centrifugal retention capacity, and difficulty in synergistically improving water absorption performance and structural strength of existing water-absorbing resins in complex soil environments, this invention proposes a magnesium-potassium composite agricultural water-absorbing resin based on magnesium ions and an organic-inorganic composite structure, as well as its preparation method.
[0010] This invention adopts the following technical solution: a method for preparing a magnesium-potassium composite agricultural water-absorbing resin, comprising the following steps: a) preparing an aqueous solution of potassium polyacrylate (CAS No.: 25608-12-2) using water (CAS No.: 7732-18-5) as a solvent; b) adding magnesium chloride hexahydrate (CAS No.: 7791-18-6) to the aqueous solution under heating and stirring conditions, so that Mg... 2+ (c) Form Mg-O coordination crosslinking points with the carboxylate groups of the potassium polyacrylate to obtain a gel-like or precipitated magnesium-potassium polyacrylate complex; (d) Dehydrate and dry the magnesium-potassium polyacrylate complex to obtain a solid magnesium-potassium composite agricultural water-absorbing resin.
[0011] In this invention, 3-methacryloyloxypropyltrimethoxysilane forms silanol groups under acidic hydrolysis conditions, which then condense or interfacially bond with the hydroxyl groups on the surface of metakaolin, thereby increasing the bonding strength between metakaolin and the organic polymer network. Acrylic acid is partially neutralized with an alkali agent before polymerization to form an acrylate / acrylic acid mixed monomer system, resulting in a polymerized network containing carboxylate groups, thus improving the hydrophilicity and water-absorbing swelling capacity of the resin network.
[0012] Preferably, the potassium polyacrylate aqueous solution in step a) is a stock solution obtained by dissolving 5 parts by mass of potassium polyacrylate in 230 parts by volume of water; in step b), 0.2-1.5 parts by mass of magnesium chloride hexahydrate are added to every 25 parts by volume of the stock solution, and the mixture is stirred at 70°C for 30 min.
[0013] Preferably, before step c), the following steps are included: d) preparing an alkaline solution with a mass ratio of sodium hydroxide (CAS No.: 1310-73-2) to water (CAS No.: 7732-18-5) of 8:100, adding polyvinyl alcohol (CAS No.: 9002-89-5) under heating conditions and stirring until homogeneous; e) adding magnesium chloride hexahydrate (CAS No.: 7791-18-6) to the solution obtained in step d) and stirring at 70°C for 30 min, so that the magnesium salt is converted in situ into magnesium hydroxide inorganic phase under alkaline conditions, wherein the magnesium hydroxide inorganic phase is dispersed in the polyvinyl alcohol system and forms a polyvinyl alcohol / magnesium hydroxide organic-inorganic composite phase with polyvinyl alcohol through surface hydroxyl action or interfacial hydrogen bonding; f) combining the magnesium-potassium polyacrylate complex obtained in step b) with the polyvinyl alcohol / magnesium hydroxide composite phase obtained in step e) and then performing dehydration and drying in step c).
[0014] Preferably, before or after step c), the step further includes preparing and introducing an organic-inorganic composite water-absorbing component, the step comprising: g) dispersing metakaolin (CAS No.: 92704-41-1) in water (CAS No.: 7732-18-5) under nitrogen (CAS No.: 7727-37-9) protection and stirring at 20°C; h) dissolving 3-methacryloyloxypropyltrimethoxysilane (CAS No.: 2530-85-0) in a mixed solvent of anhydrous ethanol (CAS No.: 64-17-5) and water to form a hydrolyzed silane solution, and... The suspension obtained in step g) was reacted at 45℃; i) xanthan gum (CAS No.: 11138-66-2) and ammonium persulfate (CAS No.: 7727-54-0) were added to the system in step h), and acrylic acid (CAS No.: 79-10-7), acrylamide (CAS No.: 79-06-1) and N,N'-methylenebisacrylamide (CAS No.: 110-26-9) were added simultaneously, and the mixture was stirred at 60±2℃ for 3 hours to form a gel; j) the gel was washed with anhydrous ethanol and dried to obtain a metakaolin-based organic-inorganic composite water-absorbing component. The parameters of the metakaolin are as follows: its main chemical composition is SiO2 and Al2O3, with an average mass fraction of 50wt% for SiO2 and 48wt% for Al2O3, and the remainder being a small amount of impurities such as Fe2O3 and TiO2; its average particle size (D50) is 2-5μm; and its specific surface area is 10-30m². 2 / g.
[0015] Preferably, the silane coupling agent in the hydrolyzed silane solution in step h) has a mass fraction of 3.0 wt%, and the volume ratio of anhydrous ethanol to water is 1:1; the reaction temperature in step h) is 45°C and the reaction time is 30 min.
[0016] Preferably, in step i), xanthan gum and ammonium persulfate are added first and stirred for 10 min, followed by the addition of acrylic acid, acrylamide and N,N'-methylenebisacrylamide and reaction at 60±2℃ for 3 h, wherein ammonium persulfate is used as a free radical initiator and N,N'-methylenebisacrylamide is used as a diene crosslinking agent.
[0017] Preferably, in step j), the gel is washed 3-4 times with anhydrous ethanol, dried at 60±2℃ to constant weight, and the dried material is pulverized and sieved to a particle size range of 100-200 mesh.
[0018] A magnesium-potassium composite agricultural water-absorbing resin, wherein the magnesium-potassium composite agricultural water-absorbing resin is prepared by the preparation method described above.
[0019] Compared to existing technologies, this invention has at least the following advantages: This invention constructs a multi-component synergistic composite water-absorbing system through the compounding of a magnesium-potassium polyacrylate complex phase, a polyvinyl alcohol / magnesium hydroxide organic-inorganic composite phase, and a metakaolin-based organic-inorganic water-absorbing component, enabling the material to possess both a high water absorption ratio and good structural stability. In this invention, Mg... 2+ Under non-strong alkaline conditions, it can form ionic coordination with the carboxylate groups on the potassium polyacrylate molecular chain, which helps to improve the bonding strength of resin particles, centrifugal retention, and resistance to dissolution and loss. Compared with the control group without magnesium salt, the sample of this invention has a lower dissolution loss rate and better centrifugal retention performance. In this invention, magnesium salt is converted into magnesium hydroxide inorganic phase in an alkaline polyvinyl alcohol system, which is dispersed in the polyvinyl alcohol phase as an inorganic reinforcing component. The structural integrity of the composite system is improved through surface hydroxyl action or interfacial hydrogen bonding, thereby improving the anti-collapse ability and particle stability of the material after water absorption. This invention introduces a metakaolin-based organic-inorganic water-absorbing component treated with a silane coupling agent. The silane coupling agent helps to enhance the interfacial bonding between the metakaolin inorganic phase and the acrylate / acrylamide copolymer network, reducing the risk of interfacial delamination during water absorption and release, so that the material can still maintain relatively good water absorption capacity in alkaline media. The resin obtained by this invention has a certain liquid absorption capacity in both deionized water and alkaline solutions. Although the water absorption rate is lower in alkaline environments due to electrolyte effects and high pH compared to deionized water systems, the sample from the examples still exhibits a high alkaline water absorption rate, indicating that its composite network structure has good environmental adaptability. The resin obtained in this invention has good soil water retention performance. Adding it to sandy loam can increase the 7-day residual water content and delay water evaporation and migration, making it suitable for applications such as agricultural water retention, drought resistance, water conservation, and fertilizer and water retention. The preparation method of this invention mainly involves aqueous phase compounding, conventional heating and stirring, dehydration, drying, pulverization, and granulation. The steps are clear, the raw materials are readily available, and it is suitable for further scale-up preparation and the widespread application of agricultural water-retaining materials. Attached Figure Description
[0020] Figure 1 This is a transmission electron microscope (TEM) image of magnesium-potassium polyacrylate complex phase powder A prepared in Example 1;
[0021] Figure 2 This is a transmission electron microscope image of polyvinyl alcohol / magnesium hydroxide composite phase powder B prepared in Example 1;
[0022] Figure 3 The infrared spectrum of the metakaolin-based organic-inorganic water-absorbing composite particle powder prepared in Example 1 is shown.
[0023] Figure 4 This is the infrared spectrum of the magnesium-potassium composite agricultural water-absorbing resin prepared in Example 1. Detailed Implementation
[0024] The present invention will be further described in detail below with reference to specific embodiments. However, these embodiments are only used to illustrate the present invention and do not constitute any limitation on the scope of protection of the present invention. For those skilled in the art, simple deductions or substitutions made without departing from the concept of the present invention should be considered as falling within the scope of protection defined by the claims of the present invention. In the present invention, unless otherwise specified, the intermediate values are used for undefined parameter ranges. In steps (4) of Examples 2 and 3, the powders are compounded according to the mass ratio of powder A: powder B: powder C = 10.8: 5.6: 61.8.
[0025] Main equipment and general conditions: (1) Magnetic stirring and heating device, stirring speed adjustable (0-1500r / min). (2) Constant temperature water bath device, temperature control accuracy ±1℃. (3) Vacuum drying oven, ultimate vacuum degree ≤-0.09MPa, temperature control accuracy ±2℃. (4) Crushing and sieving device, sieve mesh range 20-200 mesh. (5) Analytical balance, graduation value 0.1mg. (6) High-speed centrifuge, centrifugal force adjustable (0-300g). (7) Constant temperature and humidity chamber, temperature (25±1)℃, relative humidity (50±5)%.
[0026] Example 1
[0027] Step (1) Preparation of magnesium-potassium polyacrylate complex phase: Weigh 230.0 g of water and 5.0 g of potassium polyacrylate sequentially, stir at room temperature until completely dissolved to obtain a homogeneous solution; place the solution in a 70℃ constant temperature water bath and heat (heating rate 2℃ / min), after constant temperature, add 5.6 g of magnesium chloride hexahydrate in batches (1 min interval between each batch), and continue stirring at 70℃ for 30 min (stirring speed 600 r / min). After the reaction is complete, pour the system into a petri dish and spread it thinly, let it stand to room temperature; then place it in a 75℃ hot air drying oven and dry for 8 h to constant weight to obtain a sheet-like solid, pulverize and pass through a 40 mesh sieve to obtain magnesium-potassium polyacrylate complex phase powder A, the transmission electron microscope image of which is shown below. Figure 1 As shown.
[0028] Table 1 shows the raw material formula for step (1).
[0029] Table 1 Step (1) Raw material formulation (Example 1)
[0030]
[0031] Step (2) Preparation of polyvinyl alcohol / magnesium hydroxide composite phase: Weigh 25.0g of water, add 2.0g of sodium hydroxide and stir to dissolve to obtain an alkaline solution; add 5.0g of polyvinyl alcohol to the alkaline solution, heat and stir at (90±2)℃ until the polyvinyl alcohol is completely dissolved to form a homogeneous solution (40min), and then cool the system to 70℃; add 0.55g of magnesium chloride hexahydrate at 70℃ and continue stirring for 30min (stirring speed 600r / min). After the reaction, the system was poured into a petri dish and spread thinly, then dried at 25°C for 48 hours to obtain a sheet-like solid. The solid was then immersed in 200.0 g of water for 10 minutes, and the supernatant was discarded. This process was repeated twice to reduce residual soluble alkali (the above immersion treatment removes excess sodium hydroxide and the generated soluble salts from the system, avoiding interference from residual strong alkali on the subsequent water absorption and stability tests of the compounded resin). The solid was then dried at 25°C for 24 hours to constant weight, pulverized, and passed through a 40-mesh sieve to obtain polyvinyl alcohol / magnesium hydroxide composite phase powder B, the transmission electron microscope image of which is shown below. Figure 2 As shown. The structure obtained in step (2) is a multiphase composite system, and its formation mechanism includes the following synergistic effects: Mg 2+ Under alkaline conditions, it partially transforms into magnesium hydroxide and forms an inorganic phase; the polyvinyl alcohol molecular chain reacts with Mg through hydroxyl groups. 2+ Or, they interact with the surface of magnesium hydroxide; the above organic-inorganic phases form a stable composite structure through interfacial interactions.
[0032] Table 2 shows the raw material formula for step (2).
[0033] Table 2 Step (2) Raw Material Formulation (Example 1)
[0034]
[0035] Step (3) Preparation of metakaolin-based organic-inorganic water-absorbing composite particles: (3-1) Metakaolin dispersion. Weigh 150.0g of water and add it to a three-necked flask. Add 5.0g of metakaolin and stir at 20℃ for 10min (stirring speed 800r / min). At the same time, nitrogen gas is introduced as a protective gas (flow rate about 100mL / min). (3-2) Preparation of silane hydrolysis solution: Take another beaker, weigh 80.0g of anhydrous ethanol and 80.0g of water and mix them. Add 5.0g of 3-methacryloyloxypropyltrimethoxysilane while stirring, and adjust the pH of the system to 4.5 with hydrochloric acid. Continue stirring at room temperature for 10min to obtain silane hydrolysis solution (under this acidic condition, the methoxy group in 3-methacryloyloxypropyltrimethoxysilane undergoes hydrolysis to generate silanol group, which is beneficial for its subsequent condensation or interfacial bonding with the hydroxyl groups on the surface of metakaolin). (3-3) Inorganic surface modification and polymerization into gel. The silane hydrolysis solution obtained in (3-2) was added to the metakaolin suspension in (3-1) in one go. The system was heated to 45°C and stirred for 30 min (stirring speed 600 r / min). Then, 3.0 g of xanthan gum and 0.5 g of ammonium persulfate were added in sequence, and the system was stirred for 10 min while maintaining the temperature at 45°C. The system was heated to 60°C and 1.0 g of N,N'-methylenebisacrylamide, 30.0 g of acrylic acid partially neutralized by alkali and 20.0 g of acrylamide were added under nitrogen protection. The system was stirred for 3 h while maintaining the temperature at (60±2)°C (stirring speed 500 r / min) to form a gel. The degree of neutralization of acrylic acid is about 70%, and the alkali is potassium hydroxide. Specifically, under ice-water bath conditions, 16.3g of potassium hydroxide is dissolved in 20.0g of water to prepare a neutralization solution. The temperature is controlled not to exceed 30℃. The neutralization solution is slowly added to 30.0g of acrylic acid and stirred to partially neutralize, resulting in a potassium acrylate / acrylic acid mixed monomer solution with a degree of neutralization of 70%. In the preparation of agricultural water-absorbing resin, the partial neutralization of acrylic acid forms an acrylate / acrylic acid mixed monomer system, which can introduce carboxyl groups into the polymer network, improve the hydrophilicity and charge repulsion of the resin network, thereby promoting the swelling of the three-dimensional network and increasing the water absorption ratio. If the acrylic acid is not neutralized or the neutralization is too low, the interchain hydrogen bonding of the resulting polyacrylic acid is stronger, the network swelling is limited, and the water absorption ratio is reduced. (3-4) Washing, drying and particle size treatment. The obtained gel was cut into pieces of approximately 10 mm × 10 mm × 10 mm, and washed with 300.0 g of anhydrous ethanol for 10 min. The supernatant was then discarded, and this process was repeated three times. The gel was then dried in a vacuum drying oven at 60 °C to constant weight (20 h), pulverized, and passed through a 100-200 mesh sieve to obtain metakaolin-based organic-inorganic water-absorbing composite particle powder C. Its infrared spectrum is shown below. Figure 3As shown. In the preparation of agricultural water-absorbing resin, pure acrylic acid polymerizes to form polyacrylic acid, whose polymer chains have extremely strong hydrogen bonds, which leads to a significant decrease in water absorption rate. It is necessary to partially neutralize it into acrylate (such as potassium acrylate), and only by utilizing the mutual repulsion of like charges can the three-dimensional network be opened to achieve high water absorption rate.
[0036] Step (3) The formulas are listed below according to the sub-steps.
[0037] Table 3 Step (3-1) Raw Material Formulation (Example 1)
[0038]
[0039] Table 4. Step (3-2) Raw Material Formulation (Example 1)
[0040]
[0041] Table 5 shows the solid / monomer formulation added in step (3-3) (Example 1).
[0042]
[0043] Table 6. Washing solvent dosage for steps (3-4) (Example 1)
[0044]
[0045] Step (4) Composite granulation and drying molding: Weigh 10.8g of powder A, 5.6g of powder B, and 61.8g of powder C and place them in a mixer to dry mix for 5 minutes (stirring speed 300r / min); then add 6.0g of water in 3 sprays and continue mixing for 10 minutes to form wet granules; place the wet granules at 40℃ and dry for 12 hours until constant weight, sieve to obtain 20-40 mesh particles, and obtain magnesium potassium composite agricultural water-absorbing resin (sample of Example 1), whose infrared spectrum is shown below. Figure 4 As shown.
[0046] Table 7 Step (4) Compounding and Granulation Formulation (Example 1)
[0047]
[0048] The measured yield of the final dried product in Example 1 was 78.0g.
[0049] Example 2
[0050] Compared with Example 1, Example 2 only reduced the amount of magnesium chloride hexahydrate in step (1), while the other unspecified conditions were the same as in Example 1.
[0051] Table 8. Differences between Example 2 and Example 1 (Step (1))
[0052]
[0053] Example 3
[0054] Compared with Example 1, Example 3 only increased the amount of magnesium chloride hexahydrate in step (1), while the other unspecified conditions were the same as in Example 1.
[0055] Table 9. Differences between Example 3 and Example 1 (Step (1))
[0056]
[0057] Comparative Example 1
[0058] Compared with Example 1, Comparative Example 1 did not add magnesium chloride hexahydrate in step (1), and the remaining steps were the same as in Example 1, and the sample was prepared under the same granulation conditions.
[0059] Table 10. Differences between Comparative Example 1 and Example 1 (Step (1))
[0060]
[0061] Comparative Example 2
[0062] Compared with Example 1, Comparative Example 2 did not introduce powder C in steps (3) and (4), but only prepared the sample by compounding powder A and powder B; the remaining steps were the same as in Example 1 (where the amount of water used for granulation was 1.5g).
[0063] Table 11. Differences between Comparative Example 2 and Example 1 (Step (4))
[0064]
[0065] Comparative Example 3
[0066] Compared with Example 1, Comparative Example 3 did not add 3-methacryloxypropyltrimethoxysilane in step (3), and the remaining steps were the same as in Example 1 (corresponding to metakaolin-based composite water-absorbing particles without silane coupling modification), and the samples were prepared under the same granulation conditions.
[0067] Table 12. Differences between Comparative Example 3 and Example 1 (Steps (3-2))
[0068]
[0069] Comparative Example 4
[0070] Compared with Example 1, Comparative Example 4 adjusts the amount of magnesium chloride hexahydrate in step (1) to a higher value than the range of the Example, while the rest of the steps are the same as in Example 1.
[0071] Table 13. Differences between Comparative Example 4 and Example 1 (Step (1))
[0072]
[0073] Test methods
[0074] Free water absorption ratio test: The test was conducted at (25±1)℃. Weigh 0.2000g of dry resin sample and put it into a pre-weighed polyester gauze mesh bag. Record the total mass of the mesh bag and the dry sample as m2. Immerse the mesh bag in 1000.0g of deionized water and let it stand to absorb water for 120min. After the water absorption is completed, take out the mesh bag and hang it for drip filtration for 10min. Weigh the total mass of the mesh bag and the sample after water absorption and record it as m3. The free water absorption ratio Q is calculated according to formula (1): Q=(m3-m2) / m0 (1); where Q is the free water absorption ratio, in g / g; m0 is the mass of the dry resin sample, in g; m2 is the total mass of the mesh bag and the dry sample, in g; m3 is the total mass of the mesh bag and the sample after water absorption, in g.
[0075] Water absorption ratio test of alkaline solution: The alkaline solution was prepared as follows: 9.0 g of sodium hydroxide was weighed and added to 991.0 g of deionized water. After stirring until completely dissolved, the solution was cooled to (25±1)℃ for later use. 0.2000 g of dried resin sample was weighed and placed into a pre-weighed polyester gauze mesh bag. The total mass of the mesh bag and the dry sample was recorded as m2. The mesh bag was immersed in 1000.0 g of the above alkaline solution and allowed to stand for 120 min to absorb the liquid. After absorption, the mesh bag was removed and suspended for drip filtration for 10 min. The total mass of the mesh bag and the sample after absorption was weighed and recorded as m3'. The water absorption ratio of the alkaline solution, Qb, is calculated according to formula (2): Qb = (m3' - m2) / m0 (2); where Qb is the water absorption ratio of the alkaline solution, in g / g; m0 is the mass of the dried resin sample, in g; m2 is the total mass of the mesh bag and the dry sample, in g; and m3' is the total mass of the mesh bag and the sample after absorbing the alkaline solution, in g.
[0076] Centrifugation retention test: Weigh 0.2000g of dry resin sample and put it into a pre-weighed polyester gauze mesh bag. Immerse it in 1000.0g of deionized water at (25±1)℃ and let it stand for 120min to absorb water. After water absorption, take out the mesh bag and hang it for drip filtration for 10min; then place the mesh bag in a centrifuge and centrifuge for 3min at a centrifugal force of 250g. After centrifugation, take out the mesh bag and weigh it, and record it as m4. The centrifugation retention CRC is calculated according to formula (3): CRC=(m4-m2) / m0 (3); where, CRC is the centrifugation retention, in g / g; m0 is the mass of dry resin sample, in g; m2 is the total mass of mesh bag and dry sample, in g; m4 is the total mass of mesh bag and sample after centrifugation, in g.
[0077] Dissolution loss rate test: Weigh 1.0000g of dried resin sample and place it in 500.0g of deionized water. Soak for 24h at room temperature. After soaking, take out the sample, filter it, and rinse it with deionized water until the conductivity of the filtrate is basically stable. Dry the obtained solid under vacuum at 60℃ to constant weight, weigh it, and record it as m5. The dissolution loss rate L is calculated according to formula (4): L=〔(m1-m5) / m1〕×100% (4); where L is the dissolution loss rate, in %; m1 is the initial mass of the dried resin sample, in g; m5 is the mass of the sample obtained after soaking, filtering, rinsing and drying to constant weight, in g. In this test, m1=1.0000g.
[0078] Soil water retention performance test: Take 500.0g of air-dried sandy loam soil that has passed through a 2mm sieve, add 2.0g of resin sample, and mix thoroughly; then add 200.0g of deionized water to fully moisten the soil sample. Place the treated soil sample in an environment with a temperature of (25±1)℃ and a relative humidity of (50±5)% for natural evaporation for 7 days, and weigh the total mass of the soil sample after 7 days, which is recorded as m6. When adding the resin sample, the residual water volume W7 after 7 days is calculated according to formula (5): W7=m6-(500.0+2.0)(5;where, W7 is the residual water volume after 7 days, in g; m6 is the total mass of the soil sample after 7 days, in g. The blank control group does not add resin sample, and the other conditions are the same. The residual water volume of the blank control group after 7 days is calculated according to formula (6): W7=m6-500.0(6).
[0079] Test Results
[0080] The results of the water absorption and structural stability tests are shown in the table below.
[0081] Table 14 Results of Water Absorption and Structural Stability Tests
[0082]
[0083] The results of the soil water retention test are shown in the table below.
[0084] Table 15 Soil water retention test results (7-day residual water content W7)
[0085]
[0086] Results Analysis and Mechanism Explanation: As shown in Table 14, the free water absorption ratio of Example 1 was 57.8 g / g, the alkaline water absorption ratio was 42.6 g / g, the centrifugal retention was 46.2 g / g, and the dissolution loss rate was 4.2%, indicating that it had a good balance between water absorption capacity, water retention capacity after water absorption, and anti-dissolution loss performance. In alkaline solution, the water absorption ratio of each sample was lower than that in deionized water, which is consistent with the general rule that the water absorption capacity of superabsorbent polymers decreases under electrolyte and high pH environments. This is because ions in alkaline media weaken the osmotic pressure difference inside and outside the polyelectrolyte network and compress the electric double layer around the carboxylate groups, thereby limiting the further swelling of the resin network. Example 1 still maintained a water absorption ratio of 42.6 g / g in alkaline solution, indicating that its composite network structure has good structural stability in alkaline environment. Comparing Examples 1, 2, and 3, it can be seen that the amount of magnesium chloride hexahydrate in step (1) has a significant impact on the water absorption ratio and structural stability of the material. In Example 2, the amount of magnesium salt was relatively low, increasing the free water absorption ratio to 60.5 g / g, but the centrifugal retention decreased to 40.7 g / g, and the dissolution loss rate increased to 8.6%. In Example 3, the amount of magnesium salt was relatively high, decreasing the free water absorption ratio to 52.1 g / g, but increasing the centrifugal retention to 48.8 g / g, and reducing the dissolution loss rate to 3.5%. These results indicate that appropriately increasing the amount of magnesium salt helps enhance the structural stability of the magnesium-potassium polyacrylate complex phase, but excessive crosslinking or complexation will limit the network expansion space, causing a decrease in the free water absorption ratio. Comparative Example 1 did not add magnesium chloride hexahydrate in step (1), and its free water absorption ratio was 55.2 g / g, not significantly different from Example 1, but the centrifugal retention decreased to 36.8 g / g, and the dissolution loss rate increased to 11.6%. This shows that the main role of magnesium salt is not simply to increase the free water absorption ratio, but to enhance the particle bonding strength and anti-loss ability through the magnesium-potassium polyacrylate complex phase, thereby improving the water retention stability after water absorption. Comparative Example 2, without the introduction of metakaolin-based organic-inorganic water-absorbing component C, showed a decrease in its free water absorption ratio to 32.4 g / g, alkaline water absorption ratio to 21.5 g / g, and centrifugal retention to 24.3 g / g. This indicates that the acrylate / acrylamide copolymer network in component C is an important structural unit for improving water absorption capacity, while the metakaolin inorganic phase helps improve the skeletal support and structural stability of the composite particles. Comparative Example 2 still exhibited some water absorption capacity, indicating that the magnesium-potassium polyacrylate complex phase and the polyvinyl alcohol / magnesium hydroxide composite phase provide basic liquid absorption and water retention, but relying solely on this structural component is insufficient to achieve the comprehensive performance of Example 1. Comparative Example 3, without the addition of a silane coupling agent, showed a free water absorption ratio of 53.6 g / g, a limited decrease compared to Example 1, but the alkaline water absorption ratio decreased to 31.6 g / g, the centrifugal retention to 39.5 g / g, and the dissolution loss rate increased to 6.9%.This indicates that the main function of the silane coupling agent is to enhance the interfacial bonding between the inorganic phase and the organic copolymer network of metakaolin, reducing water absorption, water release, and interfacial peeling and local structural damage under alkaline media, rather than directly altering the osmotic pressure characteristics in alkaline media. In Comparative Example 4, the excessive amount of magnesium chloride hexahydrate resulted in a decrease in its free water absorption ratio to 38.6 g / g and its alkaline water absorption ratio to 25.8 g / g. Although its dissolution loss rate was low at 3.0%, its water absorption capacity and soil water retention effect were lower than those of the Example group. This result indicates that excessive magnesium salts can lead to excessively strong complexing or cross-linking, resulting in an overly dense network structure that restricts water diffusion and network expansion, thus making it difficult to obtain a high water absorption ratio. Table 15 shows that the residual water content of the blank control soil sample after 7 days was 45.2 g, while the residual water content increased to 86.7 g after 7 days after adding the resin from Example 1, indicating that the resin of this invention can effectively delay soil moisture evaporation and migration. The residual water content of Example 3 after 7 days was 89.6 g, slightly higher than that of Example 1, possibly due to its higher centrifugation retention and lower dissolution loss rate. The residual water content of Example 2 after 7 days was 80.4 g, lower than that of Example 1, indicating that although its free water absorption ratio was higher, its structural stability and water retention capacity after absorption were weaker, resulting in a decrease in the long-term water retention effect of the soil. The soil water retention effect of each comparative example was lower than that of the example group. Among them, the residual water content of Comparative Example 2 after 7 days was 61.8 g, indicating that the lack of metakaolin-based organic-inorganic water-absorbing components significantly reduced the material's water absorption capacity and contribution to soil water holding. The residual water contents of Comparative Examples 1 and 3 after 7 days were 70.5 g and 74.2 g, respectively, indicating that the lack of magnesium-potassium polyacrylate complex structure or silane interface reinforcement would weaken the stable water retention effect of the resin in the soil. The residual water content of Comparative Example 4 after 7 days was 68.6 g, indicating that although excessive magnesium salt dosage can reduce dissolution loss, it will affect the actual soil water retention performance due to insufficient water absorption capacity.
[0087] In summary, this invention achieves a good overall balance between water absorption ratio, liquid retention capacity under alkaline conditions, centrifugal retention, resistance to dissolution and loss, and soil water retention capacity through the synergistic effect of the magnesium-potassium polyacrylate complex phase, the polyvinyl alcohol / magnesium hydroxide inorganic reinforcing phase, and the metakaolin-based organic-inorganic water-absorbing components. The above results demonstrate that each component and its dosage range have a clear impact on the material properties; the absence of key components or parameters exceeding suitable ranges will lead to a decline in overall performance.
Claims
1. A method for preparing a magnesium-potassium composite agricultural water-absorbing resin, characterized in that, Includes the following steps: a) Prepare an aqueous solution of potassium polyacrylate using water as a solvent; b) Add magnesium chloride hexahydrate to the above aqueous solution under heating and stirring conditions, so that Mg... 2+ (c) Form Mg-O coordination crosslinking sites with the carboxylate groups of potassium polyacrylate to obtain a gel-like or precipitated magnesium-potassium polyacrylate complex; (d) Dehydrate and dry the magnesium-potassium polyacrylate complex to obtain a solid magnesium-potassium composite agricultural water-absorbing resin.
2. The preparation method of the magnesium-potassium composite agricultural water-absorbing resin according to claim 1, characterized in that: In step a), the potassium polyacrylate aqueous solution is a stock solution obtained by dissolving 5 parts by mass of potassium polyacrylate in 230 parts by volume of water; in step b), 0.2-1.5 parts by mass of magnesium chloride hexahydrate are added to every 25 parts by volume of the stock solution, and the mixture is stirred at 60-80°C for 20-40 min; in step c), the mixture is dried at 20-80°C for 8-48 h.
3. The preparation method of the magnesium-potassium composite agricultural water-absorbing resin according to claim 1, characterized in that: Before step c), the following steps are also included: d) preparing an alkaline solution with a sodium hydroxide to water mass ratio of (2-10):100, adding polyvinyl alcohol under heating conditions and stirring until homogeneous; e) adding magnesium chloride hexahydrate to the solution obtained in step d) and stirring at 60-80℃ for 30 min, so that the magnesium salt is converted in situ into magnesium hydroxide inorganic phase under alkaline conditions, wherein the magnesium hydroxide inorganic phase is dispersed in the polyvinyl alcohol system and forms a polyvinyl alcohol / magnesium hydroxide organic-inorganic composite phase with polyvinyl alcohol through surface hydroxyl action or interfacial hydrogen bonding; f) The magnesium-potassium polyacrylate complex obtained in step b) is combined with the polyvinyl alcohol / magnesium hydroxide composite phase obtained in step e) and then dehydrated and dried in step c).
4. The preparation method of the magnesium-potassium composite agricultural water-absorbing resin according to claim 3, characterized in that: The process includes, before or after step c), a step of preparing and introducing an organic-inorganic composite water-absorbing component, comprising: g) dispersing metakaolin in water under nitrogen protection and stirring at 15-30°C; h) dissolving 3-methacryloyloxypropyltrimethoxysilane in a mixed solvent of anhydrous ethanol and water to form a hydrolyzed silane solution, and reacting it with the suspension obtained in step g) at 40-50°C; i) adding xanthan gum and ammonium persulfate to the system in step h), and simultaneously adding acrylic acid, acrylamide and N,N'-methylenebisacrylamide, and stirring at 60±2°C for 2-5 hours to form a gel; j) washing the gel with anhydrous ethanol and drying it to obtain a metakaolin-based organic-inorganic composite water-absorbing component.
5. The preparation method of the magnesium-potassium composite agricultural water-absorbing resin according to claim 4, characterized in that: In step h), the mass fraction of the silane coupling agent in the hydrolyzed silane solution is 1-6 wt%, and the volume ratio of anhydrous ethanol to water is (1-5):(1-5); the reaction temperature in step h) is 40-50℃ and the reaction time is 20-40 min.
6. The preparation method of the magnesium-potassium composite agricultural water-absorbing resin according to claim 5, characterized in that: In step i), xanthan gum and ammonium persulfate are added and stirred for 5-15 minutes. Then acrylic acid, acrylamide and N,N'-methylenebisacrylamide are added and reacted at 40-80℃ for 2-4 hours. Ammonium persulfate is used as a free radical initiator and N,N'-methylenebisacrylamide is used as a diene crosslinking agent.
7. The method for preparing the magnesium-potassium composite agricultural water-absorbing resin according to any one of claims 4-6, characterized in that: In step j), the gel is washed 2-4 times with anhydrous ethanol, dried at 40-80℃ to constant weight, and the dried material is pulverized and sieved to a particle size range of 100-200 mesh.
8. A magnesium-potassium composite agricultural water-absorbing resin, characterized in that, The magnesium-potassium composite agricultural water-absorbing resin is obtained by the preparation method according to any one of claims 1-7.